Artistic green infrastructure for improved sense of place and ecological education - Kloeppel, Cody (Kansas State University, 2024)
Over the past century, worldwide rapid urbanization has caused a loss of green space which has led to the further disconnect between people and place. The disconnect of people and place also contributes to negative climatic effects such as flooding and water quality degradation. People who are not physically and emotionally attached to the land have less affinity to protect it. Studies have shown that reconnecting people to the environment around them can create a collective stewardship of the land and help preserve and protect these areas. Utilizing green infrastructure in an artful way through public space draws people in and allows for ecological education opportunities. This study addresses how artistic green infrastructure can be utilized to enhance the sense of place and provide ecological education opportunities in green spaces. The area being studied is the First Christian Church property and the adjacent residential apartment complex landscape across Grand Mere Parkway in Manhattan, Kansas. This area was chosen as it contains a natural drainageway that is considered a quasi-public space given church and day-care uses. Methodologies used to collect and assess data included a literature review analysis, a comparative precedent study and matrix, a site inventory and analysis, followed by an exploratory projective design process. Data collected included terms, concepts, and ideas from the artful rainwater and eco-revelatory design literature; precedents that sought art and education into green infrastructure and landscape design; and characteristics and attributes of precedents. Analysis of this data helped create a set of design guidelines and a precedent matrix that assisted in making design decisions. These findings offer insights into how green infrastructure can be used artistically and educationally to reconnect people to nature and contribute to the existing body of knowledge about placemaking. This study can also be used as a reference for projects attempting to accomplish similar goals.
Keywords: Public green space; Artful rainwater design; Eco-revelatory design; Placemaking; Green infrastructure; Ecological education